2017
DOI: 10.2147/ppa.s126327
|View full text |Cite
|
Sign up to set email alerts
|

Social relationships among adolescents as described in an electronic diary: a mixed methods study

Abstract: Social relationships among adolescents with mental disorders are demanding. Adolescents with depressive symptoms may have few relationships and have difficulties sharing their problems. Internet may offer reliable and easy to use tool to collect real-time information from adolescents. The aim of this study is to explore how adolescents describe their social relationships with an electronic diary. Mixed methods were used to obtain a broad picture of adolescents’ social relationships with the data gathered from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The result is of interest since Goldbaum et al [63] reported that students seek support and protection and discuss everyday events, personal concerns and problems with their peers. Adolescents are also willing to build up their social relationships [64]. However, we can ask whether a forum for openly discussing and sharing inner thoughts with peers is too intimate of a way to seek help for daily issues.…”
Section: Discussionmentioning
confidence: 99%
“…The result is of interest since Goldbaum et al [63] reported that students seek support and protection and discuss everyday events, personal concerns and problems with their peers. Adolescents are also willing to build up their social relationships [64]. However, we can ask whether a forum for openly discussing and sharing inner thoughts with peers is too intimate of a way to seek help for daily issues.…”
Section: Discussionmentioning
confidence: 99%
“…The studied intervention is based on the previously developed 26 and studied DepisNet program for adolescents. [39][40][41][42][43] It was developed by searching the relevant literature on the topic, identifying the most useful theories guiding intervention development, conducting interviews with professionals to gain a better perspective on the world of adolescents and their needs and solutions to their problems, and cooperating with nursing staff to ensure that the intervention would be adopted as part of the existing treatment environment and procedures. 26 It consists of health information, caters flexibly for the problems that adolescents commonly face in their daily lives, and a variety of selfreflective exercises.…”
Section: Interventionmentioning
confidence: 99%
“…The emergence of depression is a major health concern during adolescence; the prevalence of depression increases between the ages of 10 and 18 years [1][2][3]. The most common form of depression in adolescents and young adults is major depressive disorder, with a yearly incidence of approximately 8% [8,9].…”
Section: Depression During the Emerging Adult Yearsmentioning
confidence: 99%
“…Adolescence is often the time when depression symptoms arise; thus, adolescents may be faced with these symptoms during a developmental stage in which their abstract thinking and ability to conceptualize the future is still developing [1][2][3]. As a result, adolescents may post their experiences on social media as an outlet for expression or to seek peer support.…”
Section: The Role Of Developmentmentioning
confidence: 99%
See 1 more Smart Citation